Higher chlorzoxazone clearance in obese children compared with nonobese peers. (3rd June 2018) - Gade, C.; Dalhoff, K.; Petersen, T. S.; Riis, T.; Schmeltz, C.; Chabanova, E.; Christensen, H. R.; Mikus, G.; Burhenne, J.; Holm, J. C.; Holst, H.
Abstract : Aims: To test the in vivo activity of Cytochrome P450 (CYP) 2E1 in obese children vs . nonobese children, aged 11–18 years. Secondly, whether the activity of CYP2E1 in these patients is associated with NALFD, diabetes or hyperlipidaemia. Methods: Seventy children were divided into groups by body mass index (BMI) standard deviation score (SDS). All children received 250 mg oral chlorzoxazone (CLZ) as probe for CYP2E1 activity. Thirteen blood samples and 20‐h urine samples were collected per participant. Results: Obese children had an increased oral clearance and distribution of CLZ, indicating increased CYP2E1 activity, similar to obese adults. The mean AUC0–∞ value of CLZ was decreased by 46% in obese children compared to nonobese children. The F was was increased twofold in obese children compared to nonobese children, P  < 0.0001. Diabetic biomarkers were significantly increased in obese children, while fasting blood glucose and Hba1c levels were nonsignificant between groups. Liver fat content was not associated with CLZ Cl. Conclusion: Oral clearance of CLZ was increased two‐fold in obese children vs . nonobese children aged 11–18 years. This indicates an increased CYP2E1 activity of clinical importance, and dose adjustment should be considered for CLZ.